Iraqi Kurdistan in Middle Eastern politics (London ; New York)
xiv, 194 sayfa
Keywords: “The changes brought by the Arab Spring and ensuing developments in the Middle East have made the Kurds an important force in the region. Tel-Aviv and Washington place high hopes on Erbil to facilitate their dealings with Baghdad, Damascus, Teheran and Ankara. Kurds living in Turkey, Syria and Iran have been inspired by the successes of their brethren in Iraq who managed to gain significant independence and make remarkable achievements in state building. The idea of a greater Kurdistan is in the air. This book focuses on how the Kurds have become a new and significant force in Middle Eastern politics. International expert contributors conceptualize current developments putting them into theoretical perspective, helping us to better understand the potential role the Kurds could play in the Middle East.“ --